2019
DOI: 10.1088/1755-1315/348/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality (pathogen E. coli bacteria) in the coastal environment of Dumai City, Riau Province

Abstract: Escherichia coli is a water indicator microorganism. E. coli is found in almost water bodies such as lakes, rivers and seas that come from the feces of human and warm-blooded animals and waters contaminated with organic wastes. Microbiological quality is based on the presence of certain groups of microbes such as microbial pathogens (stomach disease), pollutants (especially E. coli), toxin producers etc. This research was conducted in October 2018. The purpose of this study was to calculate the density of E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, the density of E. coli at stations 2 and 3 (1.1 x 10 3 CFU/100 mL), known as an area prone to anthropogenic pollution (Feliatra et al 2020;Feliatra et al 2021), showed a higher coliform count because of the location near the harbor and densely settlements. Conversely, station 4 (7.45 x 10 2 CFU/100 mL) features a mangrove habitat, while station 1 (4.23 x 10 2 CFU/100 mL) is an industrial area (Lukistyowati et al 2019). Indonesia's Ministry of Environment is in line with the international regulations issued by WHO, which stipulated a maximum limit of E. coliform (≤200 CFU/100 mL) for activities in the field of aquaculture (Santé et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…However, the density of E. coli at stations 2 and 3 (1.1 x 10 3 CFU/100 mL), known as an area prone to anthropogenic pollution (Feliatra et al 2020;Feliatra et al 2021), showed a higher coliform count because of the location near the harbor and densely settlements. Conversely, station 4 (7.45 x 10 2 CFU/100 mL) features a mangrove habitat, while station 1 (4.23 x 10 2 CFU/100 mL) is an industrial area (Lukistyowati et al 2019). Indonesia's Ministry of Environment is in line with the international regulations issued by WHO, which stipulated a maximum limit of E. coliform (≤200 CFU/100 mL) for activities in the field of aquaculture (Santé et al 2004).…”
Section: Resultsmentioning
confidence: 99%